A QUALITATIVE STUDY OF USER PERCEPTION OF THE SEABANK E-WALLET APPLICATION - Riska Agustina Yanti; Hairunisa; Muhammad Fauzan (Indragiri Research Center (ingreat), 2025)
The development of financial technology has driven the increasing use of e-wallet applications as a means of non-cash transactions. One emerging digital wallet application is SeaBank, which offers convenience and speed in transactions. This study aims to analyze user perceptions of the SeaBank e-wallet application in terms of ease of use, security, and perceived benefits. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews and observations of active SeaBank application users. Informants were selected using purposive sampling, taking into account user experience in using the application. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that the majority of users have a positive perception of the SeaBank application, particularly regarding the ease of use of the interface and transaction efficiency. However, some users still have concerns regarding data security and system stability. This study is expected to contribute to application developers in improving service quality and serve as a reference for further research related to financial technology-based e-wallets..